Synthesis and Biological Properties of D-Amino Acids - Sharma, Shikha; Sahoo, Biswa M.; Banik, Bimal Krishna (Letters in Organic Chemistry, 2023)
In the past few years, scientists have learned more about how the human body uses Damino acids and how their synthesis occurs. This has rekindled interest in researching them. D-amino acids are known to be important in an extensive variety of physiologic operations taking place inside the human body. The correlation between these radicals and the physiology of human beings is that Daspartate and D-serine affect nerve signalling. Along with these, several other D-amino acids have also been linked to adjusting acquired immunity and the outcome of the gut barrier. Importantly, several conditions, including psychosis and amyotrophic lateral sclerosis, as well as age-related conditions, including cataracts and atherosclerosis, have been linked to the existence of D-amino acids within the human body. Also, there is more and more evidence that radicals interpret a role in the cause, progression, and treatment of cancer. This article will review the many approaches to synthesizing D-amino acids and their impact on the environment, animals, and the human body. In addition, scientific information addressing the methods of cytostatic action of D-amino acids as well as their prospective applications in industry and medicine, is included in this article.
Keywords: innate immune defense